Relationship between Nutritional Status and Urinary Tract Infection in Children - Siti F. Hidayati; Valentine Umboh; Shekina H. E. Rondonuwu (e-CliniC, 2022)
Abstract: Urinary tract infection (UTI) is one of the most common urinary tract diseases in children of all ages. Risk factors for UTI include age, sex, poor nutrition/nutritional status, uncircumcised boys, personal hygiene, urinary emptying dysfunction, and genitourinary tract abnormalities. It is already known that infection can worsen the nutritional status. This study aimed to evaluate the relationship between nutritional status and UTI in children, the incidence of UTI in children with under nutrition, poor nutrition, and over nutrition, and to compare the incidence of UTI in children with normal nutrition, undernutrition, poor nutrition, and over nutrition. This was a literature review study. The results showed that nutritional status and UTI had a significant relationship. Malnutrition or over nutrition could increase the incidence of UTI. Differences in the incidence of UTI in 12 articles were caused by a variety of factors, such as numbers of boys and girls in the studies, age, environment, and the ways to collect urine samples. In conclusion, there is a significant relationship between nutritional status and the incidence of UTI. Poor nutritional status especially malnutrition and over nutrition could increase the incidence of UTI.Keywords: urinary tract infection (UTI); nutritional status; malnutrition; obesityÂ Abstrak: Infeksi saluran kemih (ISK) merupakan salah satu penyakit saluran kemih yang sering terjadi pada anak dalam semua usia. Faktor risiko ISK antara lain usia, jenis kelamin, gizi buruk/status gizi, anak laki-laki yang belum disirkumsisi, kebersihan diri, disfungsi pengosongan urin, dan abnormalitas saluran genitourinaria. Telah diketahui bahwa infeksi dapat memperburuk status gizi. Penelitian ini bertujuan untuk mengetahui adanya hubungan antara status gizi dan ISK pada anak, angka kejadian ISK pada anak dengan gizi kurang, gizi buruk, dan gizi lebih, serta mengetahui perbandingan kejadian ISK pada anak dengan gizi normal, gizi kurang, gizi buruk, dan gizi lebih. Penelitian ini merupakan suatu literature review. Hasil penelitian mendapatkan adanya hubungan bermakna antara status gizi dan ISK. Malnutrisi maupun gizi lebih dapat meningkatkan angka kejadian ISK. Perbedaan kejadian ISK pada 12 literatur yang diteliti disebabkan karena berbagai faktor, seperti rasio jumlah anak laki-laki dan perempuan dalam penelitian, umur, lingkungan tempat tinggal, dan cara pengambilan sampel urin. Simpulan penelitian ini ialah terdapat hubungan bermakna antara status gizi dan kejadian ISK. Status gizi kurang terutama malnutrisi maupun gizi lebih dapat meningkatkan angka kejadian ISK.Kata kunci: infeksi saluran kemih (ISK); status gizi; malnutrisi; obesitasÂ